Food consumption changes during 2020 lockdown in Italy. Issue 2 (June 2022) - Braut, Beatrice; Migheli, Matteo; Truant, Elisa
Abstract: The lockdown imposed to limit the diffusion of COVID-19 in Italy affected the economic situation negatively. The income of many households decreased, and people were forced to stay home. Both these factors influenced food consumption: on the one hand less income means less money for purchases, on the other, the negative psychological impact of lesser income and the pandemic shifted the consumption towards alcohol and tobacco. Using survey data, this paper shows how the negative economic shock due to lockdown, together with the restrictions imposed by it, affected the consumption of food items in a region of Norther Italy.